2008
DOI: 10.1007/s11228-008-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

Gap, Excess and Bornological Convergence

Abstract: Let P 0 (X) be the nonempty subsets of a metric space X, d . Some classical convergences in P 0 (X) -such as convergence in Hausdorff distance, Attouch-Wets convergence and Wijsman convergence -have been shown to be compatible with the weak topology on P 0 (X) induced by all gap and excess functionals with fixed left argument ranging in some bornology. Here we consider an arbitrary ideal of subsets of X and compare the gap and excess topology so generated with the corresponding convergence defined in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Specifically, much interest is in the research of bornological universes that is triples (X, T , B), where T is a topology and B is a bornology on a set X. General bornological spaces play a key role in recent research of convergence structures on hyperspaces [2], [3], [26], in optimization theory [5] and in the study of topologies on function spaces [4], [29].…”
Section: Bornologies and Bornological Spacesmentioning
confidence: 99%
“…Specifically, much interest is in the research of bornological universes that is triples (X, T , B), where T is a topology and B is a bornology on a set X. General bornological spaces play a key role in recent research of convergence structures on hyperspaces [2], [3], [26], in optimization theory [5] and in the study of topologies on function spaces [4], [29].…”
Section: Bornologies and Bornological Spacesmentioning
confidence: 99%
“…where S is an element of S. Properties of these distance functions and the convergence structures they define are extensively studied in [5,6,7,16]. There is (at least) one notable difference between this construction and the construction used to define the ρ-Hausdroff distances.…”
Section: Introduction the Hausdorff Distance H(a B) Measures The Dementioning
confidence: 99%
“…Examples of these properties are the bounded compactness, the uniform local compactness, the cofinal completeness, the strong cofinal completeness, recently introduced by Beer in [6], as well as the so-called UC-ness for metric spaces. The study of all these spaces have shown to be not only interesting by themselves but also in connection with some problems in Convex Analysis, in Optimization Theory and in the setting of Convergence Structures on Hyperspaces (see for instance [7] and references therein).…”
Section: Introductionmentioning
confidence: 99%